Genomic insights into the diversity, virulence, and antimicrobial resistance of group B Streptococcus clinical isolates from Saudi Arabia - Alzayer, Maha; Alkhulaifi, Manal M.; Alyami, Ahmed; Aldosary, Mohammed; Alageel, Abdulaziz; Garaween, Ghada; Shibl, Atef; Al-Hamad, Arif M.; Doumith, Michel (Frontiers in Cellular and Infection Microbiology, 2024)
Detailed assessment of the population structure of Group B Streptococcus (GBS) among adults is still lacking in Saudi Arabia. Genome sequencing of a representative collection of GBS isolates (n = 89) from colonized and infected adults revealed high genetic diversity, represented by 28 sequence types (STs) and nine distinct serotypes, including uncommon serotypes VII and VIII. The majority of STs (n = 76) belonged to the human-associated clonal complexes (CCs) CC1 (33.71%), CC19 (25.84%), CC17 (11.24%), CC10/CC12 (7.87%), and CC452 (6.74%). Major CCs exhibited intra-lineage serotype diversity, except for hypervirulent CC17, which exclusively expressed serotype III. Virulence profiling revealed that nearly all isolates (94.38%) carried at least one of the four alpha family protein genes (alphaC, alp1, alp2/3, and rib), and 92.13% expressed one of the two serine-rich repeat surface proteins Srr1 or Srr2. In addition, most isolates harbored the pilus island (PI)-2a alone (15.73%) or in combination with PI-1 (62.92%), and those carrying PI-2b alone (10.11%) belonged to CC17. Phylogenetic analysis grouped the sequenced isolates according to CCs and further subdivided them along with their serotypes. Overall, isolates across all CC1 phylogenetic clusters expressed Srr1 and carried the PI-1 and PI-2a loci, but differed in genes encoding alpha-like proteins. CC19 clusters were dominated by the III/rib/srr1/PI-1+PI-2a (43.48%, 10/23) and V/alp1/srr1/PI-1+PI-2a (34.78%, 8/23) lineages, whereas most CC17 isolates (90%, 9/10) had the same III/rib/srr2/P1-2b genetic background. Interestingly, genes encoding the CC17-specific adhesins HvgA and Srr2 were detected in phylogenetically distant isolates belonging to ST1212, suggesting that other highly virulent strains might be circulating within the species. In contrast, the spread of resistance to macrolides and/or lincosamides across all major CCs (n = 48) was associated with the acquisition of erm(B) (62.5%, 30/48), erm(A) (27.1%, 13/48), lsa(C) (8.3%, 4/48), and mef(A) (2.1%, 1/48) genes, whereas resistance to tetracycline was largely mediated by the presence of tet(M) (64.18%, 43/67) and tet(O) (20.9%, 14/67) alone or in combination (13.43%, 9/67). Resistance to erythromycin, gentamicin, levofloxacin, and tetracycline was detected in only three ST19 isolates. These findings underscore the necessity for more rigorous characterization of GBS isolates causing infections.